Traditional Chinese Medicine Containing Arsenic Treated MDS Patients Effectively through Regulating Aberrant Hypomethylation - Zhou, Qing-bing (Evid Based Complement Alternat Med, 2020)
Aberrant hypermethylation and hypomethylation both play important roles in myelodysplastic syndrome (MDS). Hypomethylating agents targeting hypermethylation have been employed for the MDS treatment, but the treatment effect is limited. Novel drugs for DNA hypomethylation-targeted therapy may be needed to improve clinic efficacy for the treatment of MDS. Chinese medicine (CM) herbs have been used to treat MDS for many years in our hospital. However, the long-term treatment effect and mechanism remain unclear. In this study, all 135 patients received CM treatment for at least 36 months. The response rates for CM treatment were 81.53% (106/130) for hematological improvement in 130 MDS-RCMD patients and 80% (4/5) for bone marrow CR in 5 MDS-RAEB patients, respectively. The Human Methylation 850K BeadChip showed that 115 genes (50.88%) were aberrantly hypomethylated in 5 MDS patients compared with 3 healthy individuals. GO-analysis showed that these hypomethylated genes participated in many cancer-related biological functions and pathways. Furthermore, 60 genes were hypermethylated and the protein expression level of DNMT1 was significantly increased in the 5 MDS patients after 6 months of CM treatment. Our study suggests that CM can improve aberrant hypomethylation by increasing DNMT1 expression in MDS. The data support the clinical application of CM herbs containing arsenic as an innovative hypermethylation-inducing regimen for the treatment of MDS.